4

I have this set of equations and they are taking too much space.

What are some suggestions to make them more compact?

\begin{equation}
b_s(t) = \bm{p}_s \exp \left(-t \bm{B}_s\right)\bm{B}_s \bm{e}_s',
\end{equation}
where 
\begin{equation}
\bm{B}_s =  (\bm{B}_1 \oplus \bm{R}_2) - \lambda_R \bm{e}'( \bm{p}_1     
\otimes \bm{r}_2),
\end{equation}
\begin{displaymath}
\bm{p}_s = (1 - \rho_s)(\bm{p}_1 \otimes \bm{r}_2)\bm{K},
\end{displaymath}
\begin{displaymath}
\rho_s = \lambda_R ( \bm{p}_1 \otimes \bm{r}_2) (\bm{B}_1 \oplus    
\bm{R}_2)^{-1} \bm{e}_s',
\end{displaymath}
\begin{displaymath}
\bm{K}_s = (\bm{I} - \bm{U}_s)^{-1},\ \ \ \bm{U}_s = \bm{A}_s^{-1},
\end{displaymath}
\begin{displaymath}
\bm{A}_s = \bm{I} + \frac{1}{\lambda_R}( \bm{B}_1 \oplus \bm{R}_2) -    
\bm{e}' ( \bm{p}_1 \otimes \bm{r}_2 ),
\end{displaymath}
\begin{displaymath}
\bm{R}_2 = \bm{B}_2 - \lambda_A\bm{Q}_2,
\end{displaymath}
 \begin{displaymath}
 \bm{r}_2 = (1 - \rho_2)\lambda_A \bm{p}_2\bm{K}_2,\ 
\end{displaymath}
\begin{displaymath}
\rho_2 = \lambda_A \bm{p}_2 \bm{V}_2 \bm{e}_2,
\end{displaymath}
\begin{displaymath}
\bm{K}_2 = (\bm{I} - \bm{U}_2)^{-1},\ \ \ \bm{U}_2 = \bm{A}_2^{-1},
\end{displaymath}
\begin{displaymath}
\bm{A}_2 = \bm{I} + \frac{1}{\lambda_A}\bm{B}_2 -  \bm{e}_2' \bm{p}_2.
\end{displaymath}

UDPATE:

Ok. So I used the "gather" command and it looks better. But there are still spaces. See below...enter image description here

| improve this question | | | | |
8

The equation (and displaymath) environment leaves some space above and below by default. Since you have used many of them consecutively, they add up. You should use the align environment to avoid excessive spacing you are getting.

Next time, please post a fully compilable code so that it helps others.

\documentclass[11pt]{article}
%
\usepackage{mathtools} 
\usepackage{esvect} 
\usepackage{amssymb}
\usepackage{bm}

\begin{document}

\begin{align}
b_s(t) &= \bm{p}_s \exp \left(-t \bm{B}_s\right)\bm{B}_s \bm{e}_s', \\
\shortintertext{where}
\bm{B}_s &=  (\bm{B}_1 \oplus \bm{R}_2) - \lambda_R \bm{e}'( \bm{p}_1     
\otimes \bm{r}_2), \\
\bm{p}_s &= (1 - \rho_s)(\bm{p}_1 \otimes \bm{r}_2)\bm{K}, \notag \\
\rho_s &= \lambda_R ( \bm{p}_1 \otimes \bm{r}_2) (\bm{B}_1 \oplus    
\bm{R}_2)^{-1} \bm{e}_s', \notag \\
\bm{K}_s &= (\bm{I} - \bm{U}_s)^{-1},\ \ \ \bm{U}_s = \bm{A}_s^{-1},
\notag \\
\bm{A}_s &= \bm{I} + \frac{1}{\lambda_R}( \bm{B}_1 \oplus \bm{R}_2) -    
\bm{e}' ( \bm{p}_1 \otimes \bm{r}_2 ), \notag \\
\bm{R}_2 &= \bm{B}_2 - \lambda_A\bm{Q}_2, \notag \\
 \bm{r}_2 &= (1 - \rho_2)\lambda_A \bm{p}_2\bm{K}_2,\  \notag \\
\rho_2 &= \lambda_A \bm{p}_2 \bm{V}_2 \bm{e}_2, \notag \\
\bm{K}_2 &= (\bm{I} - \bm{U}_2)^{-1},\ \ \ \bm{U}_2 = \bm{A}_2^{-1},
\notag \\
\bm{A}_2 &= \bm{I} + \frac{1}{\lambda_A}\bm{B}_2 -  \bm{e}_2'
\bm{p}_2.\notag 
\end{align}

\end{document}

The output: enter image description here

| improve this answer | | | | |
  • This is useful, but I don't like everything aligned. I tried using the "gather" command, and it works similar, but I still have spaces. What do you suggest – PiE Apr 15 '17 at 4:04
  • 1
    @PMF: Replace align with gather and remove the alignment points specified by the &. That is, don't have consecutive display math environments. – Peter Grill Apr 15 '17 at 5:17

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.